Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Home Center Indonesia, DC Jababeka Divisi Quality Control - Martiano Dusy Charlesman; Wachid Hasyim (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Employee performance is the true foundation of a company, because without good performance, the company's goals cannot be achieved optimally. This study aims to explain the influence of organizational culture and work discipline on employee performance at PT. Home Center Indonesia DC Jababeka Quality Control Division, both partially and simultaneously. The approach used is descriptive and quantitative. The population and sample of the study were all 60 employees of PT. Home Center Indonesia DC Jababeka Quality Control Division using non-probability sampling with a census (saturated sampling) technique. Data were analyzed using multiple linear regression. The results showed that organizational culture has a positive and significant effect on employee performance (t-count = 4.581 > t-table = 1.671; sig. 0.000). Work discipline has a positive and significant effect on employee performance (t-count = 5.206 > t-table = 1.671; sig. 0.000). Simultaneously, both variables have a positive and significant effect on employee performance (F-count = 60.335 > F-table = 3.156; sig. 0.000). The total influence of both variables is 67.9% (R² = 0.679), while the remaining 32.1% is influenced by other variables outside the study.